2014
DOI: 10.1002/jcph.284
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of gastric mucosal injury induced by anti‐platelet drugs by famotidine

Abstract: Anti-platelet drug-induced gastric mucosal injury correlates with intragastric pH. Our aim was to investigate prophylaxis effects of famotidine, one of the representative histamine-2 receptor antagonists (H2RA), on gastric mucosal injury induced by dual therapy with low-dose aspirin and clopidogrel in relation to Helicobacter pylori (H. pylori) infection and CYP2C19 genotypes. This study was conducted for 20 healthy Japanese volunteers (10 H. pyloripositive and 10-negative subjects) with 100 mg aspirin plus 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Ischemic stroke patients generally need life-long use of antiplatelet or anticoagulation for secondary prevention of cardiovascular events. Aspirin is most frequently prescribed antiplatelet, which cause gastric mucosal injury [21]. Concomitant use of non-steroidal anti-inflammatory drugs (NSAID) is also common in patients with cardiovascular risk factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke patients generally need life-long use of antiplatelet or anticoagulation for secondary prevention of cardiovascular events. Aspirin is most frequently prescribed antiplatelet, which cause gastric mucosal injury [21]. Concomitant use of non-steroidal anti-inflammatory drugs (NSAID) is also common in patients with cardiovascular risk factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…Uotani et al reported that anti-platelet drug-induced gastric injury was alleviated by famotidine without attenuation of antiplatelet functions. 22 However, the sample size in their study was only 20, and the subjects were all young, healthy volunteers, not CHD patients after undergoing PCI and taking DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…The article of Martínez‐Quintana et al suggests that CYP2C19 genotype or concurrent omeprazole use does not affect outcome in PCI patients receiving clopidogrel. Uotani et al investigated the use of famotidine (which does not inhibit CYP2C19 or CYP3A isozymes) to prevent gastric mucosal injury by antiplatelet agents, suggesting that alternatives to PPIs may be useful to reduce the risk of GI bleed when using aspirin + clopidogrel. Horenstein et al notes that larger doses of clopidogrel may be indicated in patients with reduced CYP2C19 activity .…”
mentioning
confidence: 99%